Texas manok a.t.b.p., inc - Dizon, Martin Mario M. (Animo Repository, 2001)
The Philippine fast-food industry was one of the fastest growing industries in the country during the past two decades. In the same period, this sector has undergone significant structural and organizational changes in response to the changing demand of the Filipino consumers. Through research and development, and sales and marketing efforts, fast-food restaurant have continued to introduce break-through products that changes the ways the consumers take their daily meals. Fast food refers to food preparation that can be served in less than five minutes from the time an order is placed. These are consumer items such a burgers, chickens, sandwiches, pizza, donuts, and noodles. A fast food outlet has a distinct motif that could be easily recognized by customers. An outlet is generally a cool, clean, colorful, and very cheery place where people are given quick and lively services. It has a well-designed internal and external appearance that attracts customers. Texas Manok A.T.B.P (Texas Manok) is the owner, and exclusive developer and operator of Texas Chicken restaurant nationwide. The company (Texas Manok) is a wholly owned subsidiary of Vitarich Corporation, a domestic corporation engaged in feeds, livestock, and food franchising business. Through its parent company (Vitarich Corporation), Texas Manok is under a development and franchising agreement with Americas Favorite Chicken Company, the operator of more than 2,000 Churchs Popeyes, and Texas Chicken restaurants worldwide and the second largest fried chicken fast-food chain in the U.S today, to develop and operate 100 restaurant outlets in the country. At present, the company (Texas Manok) operates a total of 23 outlets nationwide, with an additional one store to be opened by January 2001.